The Knowledge Foundation for the Vocational Rehabilitation and the Integration of the Disabled People in Society - Saleh, Zainab; Hassan , Wasan (Al-Adab Journal, 2025)
The current research is one of the most important types of research concerning vocational rehabilitation for the disabled. This is because of the significant lack of researches which combine rehabilitation and integration processes in one article. The research is also a scientific reference for researchers and students working in this field. In addition, this article increases the reader's knowledge about the connection between rehabilitation and integration. The methodology of the research includes gathering information from literature concerning the rehabilitation and those concerning integration, then summarizing and arranging them in a set of paragraphs including four paragraphs for rehabilitation and another four for integration. The rehabilitation paragraphs are related to the objectives, the principles, the stages and the programs of rehabilitation, as the rehabilitation process is a systematic process that are executed in dedicated institutions with the supervision of a specialized team such as the social worker, doctor, professional expert, and psychologist, who cooperate together in their relevant fields of knowledge in order to accomplish the desired goals. The title of these paragraphs is the knowledge foundation for vocational training. The other four paragraphs are related to the elementary trends about the integration process, focusing on its objectives, the bases of its success and its types. The researchers have concluded that the interdependence between vocational rehabilitation and the integration of the disabled people is quite vital as one of the objectives of the vocational rehabilitation process is to empower the trainee and integrate them into society. The research also suggests that combining the rehabilitation and integration processes will achieve substantial gains, such as employing the disabled people after their graduation from rehabilitation institutions.